Tra storia e mistificazione. La polemica contro il mito garibaldino nel romanzo di Vincenzo Consolo Il sorriso dell’ignoto marinaio alla luce di recenti studi - Chmiel, Aneta (Romanica Silesiana)
The purpose of this paper is to discuss the myth of uprisings provoked by Garibaldie, and its diversified perception in the Italian society. Not only does Vincenzo Consolo discuss the myth of the Grabaldie’s uprisings, but he also describes the betrayed poor community of Sicilian tyrannized villagers who join Garbaldie so as to improve their difficult living conditions in the countryside. The main plot is set in the 1860s, which does not correspond with the facts but is the metaphor for the present time. The author builds the climax of the plot by using a historical narrative. What is more, it should be underlined that the narration is a mixture of various idiomatic expressions and registers, so that the community’s tragedy, which is deprived of any rights, could be expressed. Key words: Garibaldie’s myth, the present time metaphor, memory, history, a betrayed character.